Analysis of Minimum Age Limitation of Candidates for Regional Head and Deputy Head As well as Candidates for Members of the DPR, DPRD and DPD in the Democratic System in Indonesia - Anugrah, Theresya Agnes (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia is a country that implements a direct election system. General election is a political process in which people elect the DPR, DPRD, DPD, and regional heads. To become a candidate for regional head or deputy regional head, age is required. Unlike other laws and regulations that regulate the minimum age to become a member of the legislature (DPR, DPRD, and DPD), the age limit is 30 years to become governor and deputy governor, and 25 years to become mayor and deputy mayor. The data used in this research method is secondary data collected through library research techniques, and all data is analyzed as qualitative data. The study shows that the law should set a minimum age limit for candidates for regional heads and their deputies to ensure that everyone has an equal opportunity to be elected as public officials. In addition, this age limit should not be used as a standard or default for public offices that require the trust of the people who are directly elected through a fair direct election process.